2009
DOI: 10.1007/s11845-009-0381-x
|View full text |Cite
|
Sign up to set email alerts
|

Birth defects among maternal first cousins in Irish families with a neural tube defect

Abstract: This study shows that two generations of distant relatives (uncles/aunts and first cousins) in NTD families have similar maternal excesses of NTDs and birth defects overall. Inheritance mechanisms favouring matrilineal transmission, currently unknown, may contribute to birth defect occurrence in these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Risks of neural tube defects (NTDs), birth defects overall, adverse pregnancy outcomes and miscarriage are significantly greater in uncles and aunts, in first cousins (FCs) and in first cousins once removed (FCOR) among families with NTDs [1][2][3][4]. Periconceptional folic acid prevents NTDs, other birth defects and birth defects overall [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Risks of neural tube defects (NTDs), birth defects overall, adverse pregnancy outcomes and miscarriage are significantly greater in uncles and aunts, in first cousins (FCs) and in first cousins once removed (FCOR) among families with NTDs [1][2][3][4]. Periconceptional folic acid prevents NTDs, other birth defects and birth defects overall [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the present study, no study has been found concerning birth defects overall among FCOR. Considering NTDs alone, there is persuasive evidence for a maternal excess; older reports are summarized in earlier publications from this study [1][2]. Two of these older studies reported significantly more NTDs in maternal versus paternal 'second cousins', presumably the offspring of first cousins, or FCOR [11][12].…”
Section: Discussionmentioning
confidence: 75%
“…It is possible that this heterogeneity includes excess occurrences of other types of birth defects in distant relatives. We have earlier shown excess rates of birth defects overall among maternal relatives (uncles/ aunts and first cousins) in two consecutive generations of Irish families with NTDs [1,2]. The question to be evaluated here was: does this matrilineal effect continue into the third generation, i.e., do maternal compared to paternal first cousins once removed in Irish families with NTDs have excess rates of birth defects?…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may indicate higher involvement of maternal genes in embryonic development than the fetal genes, and mitochondrial inheritance or genomic imprinting could be other possible explanations for this inheritance pattern. 5,7 Embryonic gene expression, including those involved in NTDs, are affected by maternal diabetes during pregnancy. Thus, inappropriate gene regulation and expression might predispose the embryo to develop a neural tube defect, and maternal diabetes would be proposed as an etiologic risk factor for NTD, although there is no evidence that it has a direct effect on LMMC.…”
Section: Discussionmentioning
confidence: 99%